Biochemical passive reactors for treatment of acid mine drainage: Effect of hydraulic retention time on changes in efficiency, composition of reactive mixture, and microbial activity. (June 2016) - Vasquez, Yaneth; Escobar, Maria C.; Neculita, Carmen M.; Arbeli, Ziv; Roldan, Fabio
Abstract: Biochemical passive treatment represents a promising option for the remediation of acid mine drainage. This study determined the effect of three hydraulic retention times (1, 2, and 4 days) on changes in system efficiency, reactive mixture, and microbial activity in bioreactors under upward flow conditions. Bioreactors were sacrificed in the weeks 8, 17 and 36, and the reactive mixture was sampled at the bottom, middle, and top layers. Physicochemical analyses were performed on reactive mixture post-treatment and correlated with sulfate-reducing bacteria and cellulolytic and dehydrogenase activity. All hydraulic retention times were efficient at increasing pH and alkalinity and removing sulfate (>60%) and metals (85–99% for Fe 2+ and 70–100% for Zn 2+ ), except for Mn 2+ . The longest hydraulic retention time (4 days) increased residual sulfides, deteriorated the quality of treated effluent and negatively impacted sulfate-reducing bacteria. Shortest hydraulic retention time (1 day) washed out biomass and increased input of dissolved oxygen in the reactors, leading to higher redox potential and decreasing metal removal efficiency. Concentrations of iron, zinc and metal sulfides were high in the bottom layer, especially with 2 day of hydraulic retention time. Sulfate-reducing bacteria, cellulolytic and dehydrogenase activity were higher in the middle layer at 4 days of hydraulic retention time. Hydraulic retention time had a strong influence on overall performance of passive reactors. Highlights: Biochemical passive treatment represents a sustainable approach for treating acid mine drainage. Hydraulic retention times had a strong influence in the sulfate-reducing bacteria and dehydrogenase activity. Long hydraulic retention time (4 d) generated higher alkalinity and excess residual sulfides in the effluent. The hydraulic retention time strongly influenced performance ​of biochemical passive reactors.